Scholarship and Social Engagement - Louay Safi (International Institute of Islamic Thought, 2019)
The theme of this editorial is inspired by the passing of a dear friend, Sulayman Nyang, whose life epitomized the nexus between scholarship and social engagement. Dr. Nyang’s life and career follows a long-held Islamic tradition stretching over a millennium. I would like to begin my reflections by citing the tradition of social engagement and social responsibility within Islamic scholarship, and then briefly examine how that tradition was upheld by Dr. Nyang and offer a synopsis of his thoughts and actions.